Graphite fluoride modified lead-copper composite catalyst, preparation method and application
By preparing a fluorinated graphite-modified lead-copper composite catalyst, the problem of limited catalytic activity of existing catalysts was solved, achieving highly efficient catalysis of ammonium perchlorate and cyclotetramethylenetetranitrate, thereby improving the combustion performance and stability of solid propellants.
Patent Information
- Application Number
- CN202510943656.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-09
- Publication Date
- 2025-11-21
AI Technical Summary
Existing catalysts have limited catalytic activity when adjusting the combustion performance of solid propellants, and are particularly difficult to catalyze simultaneously ammonium perchlorate and cyclotetramethylenetetranitrile. Moreover, their preparation processes are complex and costly.
A method for preparing a fluorinated graphite-modified lead-copper composite catalyst was adopted. Copper acetate, lead acetate and fluorinated graphite were ultrasonically dispersed and heated and stirred in a constant temperature water bath to form a composite of copper hydroxide, lead hydroxide and fluorinated graphite. The composite catalyst with high catalytic activity and broad catalytic range was prepared by calcination in a tube furnace.
It achieves highly efficient catalysis of ammonium perchlorate and cyclotetramethylenetetranitrate, reduces their decomposition peak temperature, and improves the combustion performance and stability of solid propellants.
Smart Images

Figure CN120987713A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid propellant technology, specifically relating to a fluorinated graphite-modified lead-copper composite catalyst, its preparation method, and its application. Background Technology
[0002] Solid propellants play a crucial role in weapon systems and aerospace, and are widely used as power sources for ballistic missiles, tactical missiles, and launch vehicle boosters. Their combustion characteristics have a significant impact on the rapid response capability, long range, and high-precision strike capability of weapons and equipment. Currently, most methods involve adding combustion catalysts to regulate the combustion rate and energy release of solid propellants.
[0003] In the formulation of composite additives, large amounts of ammonium perchlorate (AP) and cyclotetramethylenetetranitramine (HMX) are generally contained. Common combustion catalysts include metals and their oxides, organometallic compounds, and inorganic metal salts. However, these catalysts have the following problems: limited catalytic activity, especially for HMX, making it difficult to achieve a significant reduction in decomposition peak temperature; the preparation process of catalysts with good catalytic activity is complex and costly; the same catalyst cannot simultaneously catalyze AP and HMX, requiring the addition of multiple catalysts to achieve the regulation of solid propellant combustion performance.
[0004] Fluorinated graphite, as a graphene-based material, possesses a high specific surface area, excellent thermal conductivity, and highly chemically active fluorine atoms, which can significantly influence the safety and combustion performance of energetic materials. When fluorine-containing groups participate in combustion reactions, they greatly accelerate the reaction rate and deepen the reaction process. This holds promise for increasing the energy level of solid propellants without altering their main components and safety, demonstrating enormous application potential in the field of energetic materials. However, its poor dispersion properties limit its application in propellant technology. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a fluorinated graphite-modified lead-copper composite catalyst, its preparation method, and its application, thereby solving the technical problem of the lack of catalysts capable of simultaneously catalyzing AP and HMX.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0007] A method for preparing a fluorinated graphite-modified lead-copper composite catalyst includes the following steps:
[0008] Step 1: Prepare a fluorinated graphite suspension;
[0009] Step 2: Add the prescribed amounts of copper acetate and lead acetate to the fluorinated graphite suspension, disperse by ultrasonication, and then heat and stir in a constant temperature water bath using a heat-collecting magnetic stirrer to obtain a suspension of copper acetate, lead acetate and fluorinated graphite.
[0010] Step 3: Add copper acetate, lead acetate and fluorinated graphite suspension to the reaction vessel, place the reaction vessel in a heat-collecting magnetic stirrer for constant temperature water bath heating and stirring, and add sodium hydroxide solution dropwise to the reaction vessel during the constant temperature water bath heating and stirring process. After the reaction is completed, filter and collect the precipitate to obtain a complex of copper hydroxide, lead hydroxide and fluorinated graphite.
[0011] Step 4: Place the copper hydroxide, lead hydroxide and fluorinated graphite composite in a tube furnace and calcine to obtain the final product.
[0012] The present invention also has the following technical features:
[0013] Specifically, the mass ratio of copper acetate, lead acetate and fluorinated graphite is 1:(1-2):(1-4).
[0014] Furthermore, the mass ratio of sodium hydroxide, copper acetate, and lead acetate is (0.8–2.4):1:(1–2).
[0015] Furthermore, in step 2, the ultrasonic dispersion time is 20-40 min, the water bath temperature for constant temperature water bath heating and stirring is 40-50℃, the stirring rate is 1200-2000 r / min, and the stirring time is 20-40 min.
[0016] Furthermore, in step 3, the water bath temperature for constant temperature water bath heating and stirring is 40-50℃, and the stirring rate is 1200-2000 r / min.
[0017] Furthermore, in step 4, the calcination temperature is 240–260°C, and the calcination time is 2–4 hours.
[0018] Furthermore, step 1 includes dissolving the alkyl glycoside in water by magnetic stirring to obtain an aqueous solution of the alkyl glycoside; and dispersing the prescribed amount of fluorinated graphite powder into the aqueous solution of the alkyl glycoside by heating and stirring in a constant temperature water bath.
[0019] The mass ratio of the alkyl glycoside to water is 1:(30-50);
[0020] The mass ratio of the alkyl glycoside to the fluorinated graphite powder is 1:(0.3-0.5);
[0021] The constant temperature water bath for heating and stirring has a water bath temperature of 40-50℃, a stirring speed of 1200-2000 r / min, and a stirring time of 20-40 min.
[0022] The present invention also protects a fluorinated graphite-modified lead-copper composite catalyst, which is prepared by the above-mentioned preparation method of the fluorinated graphite-modified lead-copper composite catalyst.
[0023] This invention also protects the application of the fluorinated graphite-modified lead-copper composite catalyst described above as a solid propellant combustion performance modifier.
[0024] Preferably, the amount of the fluorinated graphite-modified lead-copper composite catalyst added is 0.5 to 1 wt.% of the solid propellant; the solid propellant includes ammonium perchlorate and cyclotetramethylenetetranitramine.
[0025] Compared with the prior art, the present invention has the following technical effects:
[0026] (I) The fluorinated graphite-modified lead-copper composite catalyst of the present invention has good catalytic activity, which can significantly improve the combustion performance of solid propellants and is conducive to the control of the combustion performance of solid propellants.
[0027] (II) The catalyst of this invention has very good stability and tolerance.
[0028] (III) The fluorinated graphite-modified lead-copper composite catalyst of the present invention has a superior catalytic effect on solid propellants, which can reduce the peak temperature of HMX decomposition by 4.6℃ and reduce the peak temperature of AP decomposition by 156.9℃. Attached Figure Description
[0029] Figure 1 The image shows the XPS spectrum of the fluorinated graphite-modified lead-copper composite catalyst prepared in Example 1.
[0030] Figure 2 The image shows the XRD pattern of the fluorinated graphite-modified lead-copper composite catalyst prepared in Example 1.
[0031] Figure 3 The DSC curves are shown before and after mixing AP and the fluorinated graphite-modified lead-copper composite catalyst prepared in Example 1.
[0032] Figure 4 DSC curves of HMX and the fluorinated graphite-modified lead-copper composite catalyst prepared in Example 1 before and after mixing.
[0033] The specific content of the present invention will be further explained in detail below with reference to the embodiments. Detailed Implementation
[0034] It should be noted that, unless otherwise specified, all raw materials used in this invention are those known in the prior art. For example, fluorinated graphite is fluorinated graphite known in the prior art.
[0035] The concept of this invention is as follows: Considering that fluorinated graphite has a high specific surface area, excellent thermal conductivity, and contains highly chemically active F atoms, which can significantly affect the safety and combustion performance of energetic materials, this invention utilizes fluorinated graphite to introduce highly active F atoms into the field of combustion catalysts, preparing a novel fluorinated graphite-modified lead-copper composite catalyst with excellent catalytic performance. By combining traditional lead-copper catalysts with fluorinated graphite materials containing a large number of highly active F atoms, the resulting composite catalyst has the advantages of both high catalytic activity and a wide catalytic range. It can catalyze both the decomposition of ammonium perchlorate and cyclotetramethylenetetranitramine, achieving efficient catalysis and precise control of the combustion performance of solid propellants.
[0036] This invention provides a method for preparing a fluorinated graphite-modified lead-copper composite catalyst, comprising the following steps:
[0037] Step 1: Prepare a fluorinated graphite suspension;
[0038] Alkyl glycosides are dissolved in water by magnetic stirring to obtain an aqueous solution of alkyl glycosides; the prescribed amount of fluorinated graphite powder is dispersed into the aqueous solution of alkyl glycosides by heating and stirring in a constant temperature water bath to obtain the final product.
[0039] The mass ratio of the alkyl glycoside to water is 1:(30-50);
[0040] The mass ratio of the alkyl glycoside to the fluorinated graphite powder is 1:(0.3-0.5);
[0041] The constant temperature water bath for heating and stirring has a water bath temperature of 40-50℃, a stirring speed of 1200-2000 r / min, and a stirring time of 20-40 min.
[0042] Step 2: Add the prescribed amounts of copper acetate and lead acetate to the fluorinated graphite suspension, disperse by ultrasonication, and then heat and stir in a constant temperature water bath using a heat-collecting magnetic stirrer to obtain a suspension of copper acetate, lead acetate and fluorinated graphite.
[0043] Preferably, the mass ratio of copper acetate, lead acetate, and fluorinated graphite is 1:(1-2):(1-4).
[0044] Preferably, the ultrasonic dispersion time is 20–40 min, the water bath temperature for constant temperature water bath heating and stirring is 40–50℃, the stirring rate is 1200–2000 r / min, and the stirring time is 20–40 min.
[0045] Step 3: Add copper acetate, lead acetate and fluorinated graphite suspension to the reaction vessel, place the reaction vessel in a heat-collecting magnetic stirrer for constant temperature water bath heating and stirring, and add sodium hydroxide solution dropwise to the reaction vessel during the constant temperature water bath heating and stirring process. After the reaction is completed, filter and collect the precipitate to obtain a complex of copper hydroxide, lead hydroxide and fluorinated graphite.
[0046] Preferably, the mass ratio of sodium hydroxide, copper acetate and lead acetate is (0.8-2.4):1:(1-2).
[0047] Preferably, the water bath temperature for constant temperature water bath heating and stirring is 40-50℃, and the stirring rate is 1200-2000 r / min.
[0048] Step 4: Place the copper hydroxide, lead hydroxide and fluorinated graphite composite in a tube furnace and calcine to obtain the final product.
[0049] Preferably, the calcination temperature is 240–260℃ and the calcination time is 2–4 hours.
[0050] In this invention, X-ray photoelectron spectroscopy (XPS) was performed using a Thermo Fisher Science Nexsa, X-ray diffraction analysis (XRD) was performed using a PANalytical Empyrean X-ray diffractometer from the Netherlands, and differential scanning calorimetry (DSC) was performed using a TA-SDT 650 from the United States.
[0051] The following are specific embodiments of the present invention. It should be noted that the present invention is not limited to the following specific embodiments. All equivalent modifications made based on the technical solutions of this application fall within the protection scope of the present invention.
[0052] Example 1
[0053] Following the above technical solution, this embodiment provides a method for preparing a fluorinated graphite-modified lead-copper composite catalyst, including the following steps:
[0054] Step 1: Weigh copper acetate, lead acetate, and fluorinated graphite according to a mass ratio of 1:1.6:2. Based on the already weighed mass of fluorinated graphite, weigh alkyl glycoside and water sequentially according to a mass ratio of alkyl glycoside to fluorinated graphite powder of 1:0.4 and a mass ratio of alkyl glycoside to water of 1:40. Then, dissolve the alkyl glycoside in water by magnetic stirring to obtain an alkyl glycoside aqueous solution. Disperse the fluorinated graphite powder into the alkyl glycoside aqueous solution by heating and stirring in a constant temperature water bath (the water bath temperature for heating and stirring is 40℃, the stirring speed is 1500r / min, and the stirring time is 20min) to obtain a uniformly dispersed fluorinated graphite suspension.
[0055] Step 2: Place copper acetate and lead acetate in the well dispersed fluorinated graphite suspension, ultrasonically disperse for 20 minutes, then transfer to a heat-collecting magnetic stirrer for constant temperature water bath heating and stirring (water bath temperature 40℃, stirring speed 1500r / min, stirring time 20 minutes). After the process, a suspension of copper acetate, lead acetate and fluorinated graphite is obtained.
[0056] Step 3: Dissolve the weighed sodium hydroxide in ultrapure water to prepare the sodium hydroxide aqueous solution; place the prepared copper acetate, lead acetate and fluorinated graphite suspension into a heat-collecting magnetic stirrer for constant temperature water bath heating and stirring (water bath temperature 40℃, stirring speed 1500r / min); use a dropper to add the prepared sodium hydroxide solution dropwise into the copper acetate, lead acetate and fluorinated graphite suspension that is being heated and stirred in a constant temperature water bath, forming uniform copper hydroxide and lead hydroxide precipitates in the suspension. After the precipitation is complete, filter and collect the precipitate, wash it three times with ultrapure water, and then dry it to obtain the copper hydroxide, lead hydroxide and fluorinated graphite composite powder;
[0057] The mass ratio of sodium hydroxide, copper acetate, and lead acetate is 1:1:1.6.
[0058] Step 4: Place the prepared copper hydroxide, lead hydroxide and fluorinated graphite composite in a tube furnace at 250°C and calcine for 3 hours. After calcineation, the product is obtained.
[0059] Product characterization:
[0060] The X-ray photoelectron spectroscopy (XPS) of the product obtained in this embodiment is as follows: Figure 1 As shown, from Figure 1 It can be seen that the main elements of the fluorinated graphite-modified lead-copper composite catalyst are C, F, Pb, Cu, and O. Based on the valence distribution of atoms, the main substances are fluorinated graphite, lead fluoride, and copper fluoride.
[0061] The X-ray diffraction (XRD) analysis of the product obtained in this embodiment is as follows: Figure 2 As shown, from Figure 2 As can be seen from the data, the main crystal diffraction peaks of the fluorinated graphite-modified lead-copper composite catalyst are lead fluoride and copper fluoride.
[0062] Example 2
[0063] This embodiment illustrates the application of the fluorinated graphite-modified lead-copper composite catalyst prepared in Example 1 as a solid propellant combustion performance modifier.
[0064] The amount of fluorinated graphite-modified lead-copper composite catalyst added is 0.5–1 wt.% of the solid propellant.
[0065] In this embodiment, the prepared fluorinated graphite-modified lead-copper composite catalyst and ammonium perchlorate (AP) were mixed at a mass ratio of 1:1 as the test group, and AP without the addition of fluorinated graphite-modified lead-copper composite catalyst was used as the control group. Differential scanning calorimetry was performed using a TA-SDT 650 (USA).
[0066] After testing, the results were obtained Figure 3 and Table 1, where, Figure 3 The DSC curves for the two groups are shown in Table 1, which contains thermal decomposition data for the two groups at a heating rate of 10℃ / min.
[0067]
[0068] Table 1. Thermal decomposition data of AP and fluorinated graphite-modified lead-copper composite catalyst before and after mixing
[0069] The decomposition peak temperature results show that the fluorinated graphite-modified lead-copper composite catalyst reduced the decomposition peak temperature of AP by 156.9℃, indicating that the fluorinated graphite-modified lead-copper composite catalyst has a significant catalytic effect on the thermal decomposition of AP.
[0070] Example 3
[0071] This embodiment illustrates the application of the fluorinated graphite-modified lead-copper composite catalyst prepared in Example 1 as a solid propellant combustion performance modifier.
[0072] The amount of fluorinated graphite-modified lead-copper composite catalyst added is 0.5–1 wt.% of the solid propellant.
[0073] In this embodiment, fluorinated graphite-modified lead-copper composite catalyst and cyclotetramethylenetetranitramine (HMX) were mixed at a mass ratio of 1:1 as the test group, and HMX without fluorinated graphite-modified lead-copper composite catalyst was used as the control group. Differential scanning calorimetry (DSC) characterization was performed using a TA-SDT 650 (USA) instrument. Figure 4 and Table 2, where, Figure 4 Table 2 shows the DSC curves for the two groups at a heating rate of 10℃ / min, and the thermal decomposition data for the two groups are also shown in Table 2.
[0074]
[0075] Table 2. Thermal decomposition data of HMX and fluorinated graphite-modified lead-copper composite catalyst before and after mixing.
[0076] The results of the decomposition peak temperature show that the fluorinated graphite-modified lead-copper composite catalyst reduced the decomposition peak temperature of HMX by 4.6℃, indicating that the fluorinated graphite-modified lead-copper composite catalyst has a catalytic effect on the thermal decomposition of HMX.
[0077] Comparative Example 1
[0078] In this comparative example, existing catalysts nano-Cu, nano-CuO, and nano-copper 2,4-dihydroxybenzoate were used to conduct catalytic tests on AP. The test results are shown in Table 3.
[0079]
[0080] Table 3. Catalytic test results of existing catalysts for AP
[0081] Comparative Example 2
[0082] In this comparative example, existing catalysts, nano-Ti, PbO, and NTO-Pb, were used to test the catalytic activity of HMX used in Example 1. The test results are shown in Table 4.
[0083]
[0084] Table 4. Catalytic test results of existing catalysts for HMX
[0085] As can be seen from Example 1, Comparative Example 1, and Comparative Example 2:
[0086] Compared with existing commonly used catalysts, the fluorinated graphite-modified lead-copper composite catalyst prepared by the method of this invention can catalyze AP and HMX, and the peak temperatures of AP and HMX decomposition peaks are reduced more significantly.
[0087] The above-described implementation process is merely an example to clearly illustrate this application and is not intended to limit the implementation methods. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively list all possible implementation methods here. However, obvious variations or modifications derived therefrom are still within the protection scope of this application.
Claims
1. A method for preparing a fluorinated graphite-modified lead-copper composite catalyst, characterized in that, Includes the following steps: Step 1: Prepare a fluorinated graphite suspension; Step 2: Add the prescribed amounts of copper acetate and lead acetate to the fluorinated graphite suspension, disperse by ultrasonication, and then heat and stir in a constant temperature water bath using a heat-collecting magnetic stirrer to obtain a suspension of copper acetate, lead acetate and fluorinated graphite. Step 3: Add copper acetate, lead acetate and fluorinated graphite suspension to the reaction vessel, place the reaction vessel in a heat-collecting magnetic stirrer for constant temperature water bath heating and stirring, and add sodium hydroxide solution dropwise to the reaction vessel during the constant temperature water bath heating and stirring process. After the reaction is completed, filter and collect the precipitate to obtain a complex of copper hydroxide, lead hydroxide and fluorinated graphite. Step 4: Place the copper hydroxide, lead hydroxide and fluorinated graphite composite in a tube furnace and calcine to obtain the final product.
2. The method for synthesizing the fluorinated graphite-modified lead-copper composite catalyst as described in claim 1, characterized in that, The mass ratio of copper acetate, lead acetate and fluorinated graphite is 1:(1-2):(1-4).
3. The method for synthesizing the fluorinated graphite-modified lead-copper composite catalyst as described in claim 1, characterized in that, In step 3, the mass ratio of sodium hydroxide, copper acetate, and lead acetate is (0.8–2.4):1:(1–2).
4. The method for synthesizing the fluorinated graphite-modified lead-copper composite catalyst as described in claim 1, characterized in that, In step 2, the ultrasonic dispersion time is 20-40 min, the water bath temperature for constant temperature water bath heating and stirring is 40-50℃, the stirring rate is 1200-2000 r / min, and the stirring time is 20-40 min.
5. The method for synthesizing the fluorinated graphite-modified lead-copper composite catalyst as described in claim 1, characterized in that, The water bath temperature for the constant temperature water bath heating and stirring in step 3 is 40-50℃, and the stirring rate is 1200-2000 r / min.
6. The method for synthesizing the fluorinated graphite-modified lead-copper composite catalyst as described in claim 1, characterized in that, In step 4, the calcination temperature is 240–260°C and the calcination time is 2–4 hours.
7. The method for synthesizing the fluorinated graphite-modified lead-copper composite catalyst as described in claim 1, characterized in that, Step 1 includes dissolving the alkyl glycoside in water by magnetic stirring to obtain an aqueous solution of the alkyl glycoside; and dispersing the prescribed amount of fluorinated graphite powder into the aqueous solution of the alkyl glycoside by heating and stirring in a constant temperature water bath. The mass ratio of the alkyl glycoside to water is 1:(30-50); The mass ratio of the alkyl glycoside to the fluorinated graphite powder is 1:(0.3-0.5); The constant temperature water bath for heating and stirring has a water bath temperature of 40-50℃, a stirring speed of 1200-2000 r / min, and a stirring time of 20-40 min.
8. A fluorinated graphite-modified lead-copper composite catalyst, characterized in that, It is prepared by any one of the preparation methods described in claims 1 to 7.
9. The application of the fluorinated graphite-modified lead-copper composite catalyst as described in claim 8 as a solid propellant combustion performance modifier.
10. The application as described in claim 9, characterized in that, The amount of the fluorinated graphite-modified lead-copper composite catalyst added is 0.5 to 1 wt.% of the solid propellant; the solid propellant includes ammonium perchlorate and cyclotetramethylenetetranitramine.